Autism assessment via telehealth during the Covid 19 pandemic: Experiences and perspectives of autistic adults, parents/carers and clinicians. (October 2021) - Gibbs, Vicki; Cai, Ru Ying; Aldridge, Fiona; Wong, Michelle
Highlights: The majority of autistic adults and parent/carers were satisfied with assessments conducted via telehealth. Clinicians were slightly less confident when delivering assessments via telehealth however overall confidence in diagnostic decision-making remained high. Assessments via telehealth are an acceptable and feasible alternative to in-person assessments from the perspective of stakeholders. Conducting pre-assessment screening may assist in determining suitability of potential recipients of telehealth assessments. Abstract: Background: The COVID-19 pandemic has seen a rapid increase in the use of telehealth to deliver services to autistic individuals and their families. Research into the provision of autism assessments via telehealth is limited and few studies have explored clinician perspectives of conducting diagnostic assessments for autism in this way. The objective of this study was to examine the acceptability of a new telehealth model from the perspective of key stakeholder groups in an Australian community-based sample i.e. clients undergoing assessment, parent/carers and expert clinicians. Methods: Sixteen adult clients ( M age = 39.00, SD age = 14.39) and fifty-six parent/carers of children and adults ( M age = 44.09, SD age = 9.87) undergoing autism assessments completed an online survey about their experiences of assessments via telehealth. Of these, six clients and twelve parent/carers agreed to participate in follow up interviews. Seven clinicians were also interviewed. Results: In this study, the majority of adults and parent/carers reported that they, or the person they cared for, felt comfortable interacting with the clinician, would be willing to undergo future assessments via telehealth and were not concerned that important information had been missed during the assessment. Although the clinicians were slightly less satisfied with tele-assessment process compared to face-to-face and relied on external sources of information more than they would during a face-to-face assessment, their overall confidence in their diagnostic decision making remained high. Conclusion: Autism assessment via telehealth may be an acceptable alternative in some circumstances. However, a telehealth service should consider screening clients for suitability and adequately preparing clients for tele-assessments.